SDMS: smart database management system for accessing heterogeneous databases. (2nd March 2021) - Mershad, Khaleel; Hamieh, Ali
Digital data are usually divided into structured and unstructured types. Although unstructured data are becoming a significant part of digital data, there are still a large number of organisations that save their data into structured datastores. However, with many companies shifting into utilising non-structural database management systems (DBMS), they find themselves obliged to translate and convert their old structured data into new forms. In order to avoid the consequences of such costly operations, we present the basics of a new database management system that allows a database user to access and query both structural and non-structural databases at the same time using a single query. We explain the details of various types of queries (insert, update, delete, and search) that are performed by the proposed system, and discuss the tests that we made to measure the end-to-end delays of these queries on two MySQL and HBase databases.